A study on contextual element of Melaka famous food spot / Nur Izzatul Hanis Hassim - Hassim, Nur Izzatul Hanis (2019)
The main objective of this research is to study on Contextual Element of Melaka Famous Food Spot in Melaka City. In this research, the researcher decided to use a qualitative method in term to collect data. There are many visitors to Malaysia every year who have no information about food diversity in here. Most restaurant they found on internet and blog does not really show the Melaka best food spot. They know Malaysia is a food paradise and well known with their citizen who love to eat but have no confident in exploring the gastronomic experience outside their comfort zone. Malaysia is the first place to be visited in Asia because of having various mix of culture and food from different race beside by its nature beauty. At the end of this research, the researcher will be able to come out with a short list of few contextual element of Melaka famous food spot that will giving benefit for foreign tourist and also local society.